Early Repolarization Syndrome; Mechanistic Theories and Clinical Correlates - Mercer, Ben N.; Begg, Gordon A.; Page, Stephen P.; Bennett, Christopher P.; Tayebjee, Muzahir H.; Mahida, Saagar (Frontiers in Physiology, 2016)
The early repolarization (ER) pattern on the 12-lead electrocardiogram is characterized by J point elevation in the inferior and/or lateral leads. The ER pattern is associated with an increased risk of ventricular arrhythmias and sudden cardiac death (SCD). Based on studies in animal models and genetic studies, it has been proposed that J point elevation in ER is a manifestation of augmented dispersion of repolarization which creates a substrate for ventricular arrhythmia. A competing theory regarding ERS proposes that the syndrome arises as a consequence of abnormal depolarization. In recent years, multiple clinical studies have described the characteristics of ER patients with VF in more detail. The majority of these studies have provided evidence to support basic science observations. However not all clinical observations correlate with basic science findings. This review will provide an overview of basic science and genetic research in ER and correlate basic science evidence with the clinical phenotype.